Corrected cholesterol, a novel marker for predicting semen post-thaw quality: a pilot study. (3rd April 2019) - Dearing, Chey G.; Lindsay, Kevin S.
Abstract: Semen cryopreservation is the recommended method for protecting the fertility of men before they undergo iatrogenic treatments. However, post-thaw sperm quality is highly variable between and within individuals. Thus, prediction of post-thaw quality has not been achieved with great certainty. Men ( n  = 101) attending our andrology clinic each produced a single ejaculate for semen analysis and semen cryopreservation. Post-thaw semen quality was examined for associations with traditional and novel semen and seminal plasma parameters. This current research demonstrates that the cholesterol concentration of human sperm is associated with ejaculate tolerance to cryopreservation. Corrected cholesterol, calculated as the difference between the cholesterol of semen and the cholesterol of cell free seminal plasma, is predictive of post-thaw motility. This may have potential as a method to guide the number of ejaculates stored for individual patients before iatrogenic treatment and/or for the appropriate selection of ART with frozen/thawed semen.